1989
DOI: 10.1093/ajcn/50.2.332
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism and vitamin A deficiency in children in northeast Thailand

Abstract: To investigate the association between vitamin A and iron metabolism, two studies were carried out: a cross-sectional study and an intervention trial. The cross-sectional analysis was carried out in 1060 children aged 1-8 y. Multiple-regression analysis was used to adjust for effects of age, gender, indices of the protein nutritional status, and infections. Retinol was significantly associated with hematocrit, serum Fe, transferrin, ferritin, and saturation of transferrin (%ST). To obtain further evidence as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
3
15

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 23 publications
2
75
3
15
Order By: Relevance
“…Vitamin A status has been shown to be poor in school-aged children in other Indian studies (Dwivedi et al, 1992;Kapil et al, 1996;Khandait et al, 1999). Nutritional surveys have shown a close association between vitamin A deficiency and anemia (Mejia and Chew, 1988;Bloem et al, 1989). Vitamin A repletion may reduce anemia by improving utilization of stored Fe for erythropoiesis (Zimmermann et al, 2006), and by enhancing immunity and reducing the anemia of infection (Semba and Bloem, 2002).…”
Section: Urban Andmentioning
confidence: 95%
“…Vitamin A status has been shown to be poor in school-aged children in other Indian studies (Dwivedi et al, 1992;Kapil et al, 1996;Khandait et al, 1999). Nutritional surveys have shown a close association between vitamin A deficiency and anemia (Mejia and Chew, 1988;Bloem et al, 1989). Vitamin A repletion may reduce anemia by improving utilization of stored Fe for erythropoiesis (Zimmermann et al, 2006), and by enhancing immunity and reducing the anemia of infection (Semba and Bloem, 2002).…”
Section: Urban Andmentioning
confidence: 95%
“…In northeast Thailand, children who received high dose vitamin A, 60 mg retinol equivalent (RE), had higher serum iron and percentage transferrin saturation compared with control children at 2 months post-supplementation, but these differences disappeared by 4 months post-supplementation (Bloem et al, 1989). Further investigation involving school children with conjunctival xerosis showed that children who received 60 mg RE vitamin A had a significant increase in hemoglobin, hematocrit, serum iron and percentage transferrin saturation at 2 weeks following supplementation, whereas no changes of these indicators occurred in the control group (Bloem et al, 1990).…”
Section: Epidemiologymentioning
confidence: 99%
“…Poor vitamin A status has been associated with low iron binding capacity and percent transferrin saturation (Mejia & Anemia of vitamin A deficiency RD Semba and MW Bloem Arroyave, 1983;Bloem et al, 1989), but not low circulating transferrin concentrations (Mejia & Arroyave, 1983). Iron metabolism was examined in a large study of preschool children, age 1 -5 y, before and after a program of vitamin A-fortified sugar (Mejia & Arroyave, 1982).…”
Section: Vitamin a And Iron Metabolismmentioning
confidence: 99%
“…The assignment to the three food groups was done randomly after strati®cation for anemia, since studies have shown that vitamin A status is positively correlated with haemoglobin (Hb) levels (Ahmed et al, 1993(Ahmed et al, , 1996Bloem et al, 1989). All 164 children were given a single supervised 500 mg dose of Mebendazole 2 weeks before initiation of the supplementation trial.…”
Section: Subjectsmentioning
confidence: 99%